ERRs Mediate a Metabolic Switch Required for Somatic Cell Reprogramming to Pluripotency - Kida, Yasuyuki S.; Kawamura, Teruhisa; Wei, Zong; Sogo, Takahiro; Jacinto, Sandra; Shigeno, Asako; Kushige, Hiroko; Yoshihara, Eiji; Liddle, Christopher; Ecker, Joseph R.; Yu, Ruth T.; Atkins, Annette R.; et al. (Cell stem cell, 2015)
Cell metabolism is adaptive to extrinsic demands; however, the intrinsic metabolic demands that drive the induced pluripotent stem cell (iPSC) program remain unclear. Although glycolysis increases throughout the reprogramming process, we show that the estrogen-related nuclear receptors (ERRα and ERRγ) and their partnered co-factors PGC-1α and PGC-1β are transiently induced at an early stage, resulting in a burst of oxidative phosphorylation (OXPHOS) activity. Upregulation of ERRα or ERRγ is required for the OXPHOS burst in both human and mouse cells, respectively, as well as iPSC generation itself. Failure to induce this metabolic switch collapses the reprogramming process. Furthermore, we identify a rare pool of Sca1−/CD34− sortable cells that is highly enriched in bona fide reprogramming progenitors. Transcriptional profiling confirmed that these progenitors are ERRγ and PGC-1β positive and have undergone extensive metabolic reprogramming. These studies characterize a previously unrecognized, ERR-dependent metabolic gate prior to establishment of induced pluripotency. [Display omitted] •ERRα/γ are transiently induced during iPSC reprogramming•An ERR-mediated OXPHOS burst is essential for somatic cell reprogramming•ERRγ and PGC-1β are selectively expressed in a Sca1−/CD34− progenitor pool•Early reprogramming Sca1−/CD34− cells have enhanced reprogramming efficiency Kida et al. show that upregulation of ERRα or ERRγ is required for a metabolic switch involving OXPHOS that is essential for iPSC generation and that early upregulation of ERRs marks cells that are destined to go on to be reprogrammed.